1986
DOI: 10.1128/jvi.58.2.296-306.1986
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a retroviruslike sequence from the TL locus of the C57BL/10 murine major histocompatibility complex

Abstract: Two retroviruslike sequences have been isolated from the TL locus of the major histocompatibility complex of C57BL/10 mice. One sequence (TLev2) hybridizes only with probes derived from the pol region of the murine leukemia provirus AKR; the other sequence (TLevl) hybridizes with gag, pol, and env AKR region probes. This 9-kilobase endogenous, TL region-associated virus (TLevl) has been further characterized. The TLevl genome has been shown to contain murine leukemia virus-related sequences bounded by retrovir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1987
1987
1996
1996

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…On tbe basis of the observation that T cells from MRL-lpr/lpr mice are resistant to antigen-induced apoptosis, abnormally low Fas expression has been proposed to impair Fas-mediated peripberal deletion of activated T cells, resulting in accumulation of aberrant T cells in MRLlpr/lpr mice (Russell et al 1993, Bossu et al 1993). Meruelo et al (1983Meruelo et al ( , 1984 demonstrated, by restriction fragment length polymorphism (RFLP) hybridization studies witb MuLV env probes, multiple integrations of ERV sequences in loci encoding lymphocyte differentiation antigens (LyI7 and Ly21 ) and major (TL region) and minor (H-3, 13, 28, 30, 38) bistocompatibility antigens in mice, some of which were cloned and sequenced and shown to be comprised of MuLV-related sequences (Pampeno & Meruelo 1986, Rossomando & Meruelo 1986. Surprisingly, hybridization of digested genomic DNA with one of the ERV sequences mapping in tbe minor histocompatibility antigen H-30 region, revealed that tbe related ERV insertions were located in the vicinity of 15 additional minor histocompatibility loci (Rossomando & Meruelo 1986).…”
Section: Retrovirus Integrationmentioning
confidence: 99%
“…On tbe basis of the observation that T cells from MRL-lpr/lpr mice are resistant to antigen-induced apoptosis, abnormally low Fas expression has been proposed to impair Fas-mediated peripberal deletion of activated T cells, resulting in accumulation of aberrant T cells in MRLlpr/lpr mice (Russell et al 1993, Bossu et al 1993). Meruelo et al (1983Meruelo et al ( , 1984 demonstrated, by restriction fragment length polymorphism (RFLP) hybridization studies witb MuLV env probes, multiple integrations of ERV sequences in loci encoding lymphocyte differentiation antigens (LyI7 and Ly21 ) and major (TL region) and minor (H-3, 13, 28, 30, 38) bistocompatibility antigens in mice, some of which were cloned and sequenced and shown to be comprised of MuLV-related sequences (Pampeno & Meruelo 1986, Rossomando & Meruelo 1986. Surprisingly, hybridization of digested genomic DNA with one of the ERV sequences mapping in tbe minor histocompatibility antigen H-30 region, revealed that tbe related ERV insertions were located in the vicinity of 15 additional minor histocompatibility loci (Rossomando & Meruelo 1986).…”
Section: Retrovirus Integrationmentioning
confidence: 99%
“…To date, however, this observation has not been made. Endogenous retroviral sequences have, however, been mapped both to the H-2 Tla region (Meruelo et al, 1984Pampeno & Meruelo, 1986 and to many minor histocompatibility loci (Meruelo er al., 1983;. The significance of these observations in the context of MHC regulation following transformation is not clear however.…”
Section: Discussionmentioning
confidence: 99%
“…Our group has long noted an association between endogenous viral sequences and genes encoding class I MHC antigens, minor histocompatibility antigens and several Ly antigens (Meruelo et al, 1983(Meruelo et al, ,1984Pampeno & Meruelo, 1986. Hybridization studies have shown that sequences hybridizing to xenotropic and ecotropic viral envelope probes are associated with Ly-17 on chromosome 1; H-3 and H-13 on chromosome 2; Ly-21 on chromosome 7; H-28 on chromosome 3; H-16 on chromosome 4; Thy-I on chromosome 9; H-30 on chromosome 15; and H-38 on chromosome 12.…”
Section: How Does Radl V Mediate Its Biological Consequences?mentioning
confidence: 99%
See 2 more Smart Citations